Effect of doping on dielectric and optical properties of barium hexaferrite: Photocatalytic performance under solar light irradiation. Issue 22 (15th November 2021) - Bibi, Ismat; Muneer, Muhammad; Iqbal, Munawar; Alwadai, Norah; Almuqrin, Aljawhara H.; Altowyan, Abeer S.; Alshammari, Fwzah H.; Almuslem, Amani Saleh; Slimani, Yassine
Abstract: A series of Co-doped and Cr-doped Ba1-x Cox Fe12-y Cry O19 nanoparticles (NPs) were synthesized via the microemulsion route. The effects of Co and Cr substitution on the structural, dielectric, optical, and photocatalytic properties of the NPs were investigated. The Ba1-x Cox Fe12-y Cry O19 NPs were characterized using Fourier-transform infrared spectroscopy, X-ray diffraction analysis, scanning electron microscopy, Raman scattering, and dielectric measurements. The Ba1-x Cox Fe12-y Cry O19 NPs were obtained in a single phase with an average crystallite size of 18 nm. The dielectric constant of the NPs decreased, while the dielectric loss and tangent loss increased with increasing dopant (Co and Cr) contents. The photocatalytic activities (PCAs) of the Ba1-x Cox Fe12-y Cry O19 and BaFe12 O19 NPs were appraised by carrying out the degradation of CV (crystal violet) dye under solar light irradiation. The doping improved the PCA of BaFe12 O19, and up to 64.23% of the CV dye could be degraded within 60 min under visible light irradiation. The Ba1-x Cox Fe12-y Cry O19 NPs showed great potential for application as an economic photocatalyst as they required solar light irradiation for the degradation of CV.